Digital versus Traditional Workflow for Posterior Maxillary Rehabilitations Supported by One Straight and One Tilted Implant: A 3-Year Prospective Comparative Study. (11th November 2018) - Ferrini, Francesco; Capparé, Paolo; Vinci, Raffaele; Gherlone, Enrico F.; Sannino, Gianpaolo
Abstract : Objectives . The aim of the study was to evaluate and compare digital and traditional prosthetic workflow for posterior maxillary restorations supported by an upright and a distally tilted implant at 3-year follow-up. Materials and Methods . Twenty-four patients were treated in the posterior maxilla with 24 immediately loaded axial and 24 distally tilted implants supporting 3-unit or 4-unit screw-retained prostheses. Three months after initial loading patients were randomly stratified into two groups: definitive traditional impressions were carried out in the control group, while digital impressions were performed in the test group. The framework-implant connection accuracy was evaluated by means intraoral digital radiographs at 3, 6, 12, and 36 months of follow-up examinations. Outcome considerations comprised implant and prosthetic survival and success rates, marginal bone level changes, and required clinical time to take impressions. Results . A total of 24 patients received immediately loaded screw-retained prostheses supported by an upright and a distally tilted implant (total 48 implants). No implant dropouts occurred, showing an overall survival rate of 100% for both groups. None of the 24 fixed prostheses were lost during the observation period (prosthetic survival rate of 100%). No statistically significant differences in marginal bone loss were found between control and test groups. The digital impression procedure required on average less clinical time than the conventional procedure. Conclusions . Clinical and radiologic results suggest that digital impression is a predictable procedure for posterior maxillary restorations supported by an upright and a distally tilted implant.